DETERMINASI PARTISIPASI POLITIK PEDAGANG SAYUR MMTC KOTA MEDAN DALAM PILKADA TAHUN 2024 - Manotar Leryaldo Sinaga; Nainggolan, Mangido; Ramsul Nababan; Windawati Pinem; Yakobus Ndona (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of political participation as an indicator of the quality of local democracy in the 2024 Medan City Regional Election. Vegetable vendors in the MMTC area, as an informal economic group, hold significant voting potential; however, the determinants of their political participation have not been extensively studied. The research problem is the factors influencing the political participation of MMTC vegetable vendors in the 2024 Regional Election. The study aims to analyze the determinants of political participation based on structural, sociological, ecological, psychosocial, and rational choice factors. The method used is qualitative descriptive. Primary data was obtained through observation and in-depth interviews with vegetable vendors as research subjects, while secondary data was sourced from relevant literature and documents. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the political participation of MMTC vegetable vendors in the 2024 Medan City Regional Election is influenced by structural, sociological, ecological, social-psychological, and rational choice factors, where structural factors are not yet dominant due to a low level of understanding of the Regional Election system, while sociological, ecological, psychosocial, and rational choice factors are the ones that more significantly influence the vendors’ political choices.